Serum thioredoxin and lactoferrin in rheumatoid arthritis and their association with rheumatoid factor - Delcheva, Ginka; Stefanova, Katya; Stankova, Teodora; Maneva, Ana (Journal of Medical Biochemistry, 2024)
Background: Thioredoxin (Trx) and lactoferrin (Lf) are multifunctional proteins part of the body anti-oxidant defence and counteract the oxidative tissue damage. The purpose of our study is to investigate Trx and Lf levels in serum of rheumatoid arthritis (RA) patients and establish the association of these proteins with the rheumatoid factor (RF) and other disease markers.Methods: The study included 114 patients with RA and 42 healthy subjects. Serum concentrations of Trx, Lf, RF, anti-cyclic citrullinated peptide (anti-CCP) antibodies, CRP, and IL-6 were determined using commercially available ELISA kits.Results: Serum thioredoxin levels in RA were significantly higher compared to the control group, 36.4 (29.6-40.2), ng/mL versus 19.0 (16.3-26.8), ng/mL, p < 0.0001. Serum lactoferrin levels were elevated in RA compared to the control group but the difference was not statistically significant, 579.6 (312.8-947.5), ng/mL versus 519.0 (262.5-928.0), ng/mL. We found significant negative correlations of Trx and Lf with rheumatoid factor in RA (r= -0.254, p=0.05 and r= -0.238, p=0.014, respectively). The correlations of thioredoxin and lactoferrin with other disease markers such as anti-CCP antibodies, DAS28, ESR, CRP, and IL-6 were not statistically significant. A strong positive correlation between Trx and Lf was observed in the study group of RA patients (r=0.519, p
Keywords: lactoferrin; oxidative stress; rheumatoid arthritis; rheumatoid factor; thioredoxin